Implementation of Collaborative Governance in Public Policy Handling COVID-19 - Muhammad Musaad (International Journal of Science and Society, 2021)
Collaborative governance seems to be a response to failures in execution, exorbitant costs, and the politicization of public sector laws. The emphasis is on all stages of public policy. The unprecedented COVID-19 epidemic has compelled the government to be prepared to deal with it, and to do so fast and effectively. To combat the epidemic, the Indonesian government has implemented a variety of strategies, including social restrictions, mandated immunizations, national economic recovery, and so on. However, the government cannot undertake Collaborative government alone; thus, cross-disciplinary and field cooperation is required. As a result, the purpose of this research is to explore the application of collaborative governance in dealing with COVID-19 in Indonesia. This research combines a qualitative methodology with a descriptive approach. According to the findings of the research, collaborative governance in the management of COVID 19 has four key values: consensus orientation, collective leadership, multi-way communication, and resource sharing. Collaborative governance in COVID-19 management may take the form of, among other things, publicizing the hazards of COVID-19, providing masks, creating and spraying disinfectants, and distributing hand sanitizers.